Repurposing colchicine's journey in view of drug-to-drug interactions. A review. (2021) - Vrachatis, Dimitrios A.; Papathanasiou, Konstantinos A.; Giotaki, Sotiria G.; Iliodromitis, Konstantinos E.; Papaioannou, Theodore G.; Stefanini, Giulio G.; Cleman, Michael; Siasos, Gerasimos; Reimers, Bernhard; Lansky, Alexandra; Tardif, Jean-Claude; Deftereos, Spyridon G.; et al.
Graphical abstract: Highlights: Colchicine is among the oldest drug molecules in medical history. Clinicians should always check for drug to drug interactions and modify colchicine's dose according to published guidelines. Beyond known indications (e.g. pericarditis, gout), current evidence implies favorable colchicine effects in CAD, stroke and even in COVID19. Abstract: Colchicine's medical evolution is historically bound to the Mediterranean basin, since remarkable researchers from this region underscored its valuable properties. With the passing of years colchicine became an essential pharmaceutical substance for the treatment of rheumatologic and cardiovascular diseases. In light of recent findings, the therapeutic value of colchicine has grown. In clinical practice, colchicine remains underutilized in view of its proven efficacy and safety. Its complex pharmacokinetics and multifaceted anti-inflammatory role remain under investigation. The current review addresses the safe administration of colchicine in view of key drug to drug interactions. Finally, we are briefly presenting colchicine's future potential applications.